(untitled) (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: Avian influenza is a zoonotic disease with a pandemic potential that can infect avian and mammalian species, including humans. Studies aimed at investigating avian influenza virus (AIV) status in asymptomatic chickens and their shedding are uncommon in Bangladesh. Therefore, the current study aimed to examine the distribution of AIV subtypes in asymptomatic commercial chicken flocks and to identify the possible risk factors associated with this infection in two selected sub-districts of Bangladesh. Materials and Methods: A total of 582 oropharyngeal swabs were collected from 23 chicken farms during 2019 and evaluated for the presence of AIV and its subtypes by real-time reverse transcription PCR assays. Risk factors associated with AIV infection were analyzed from questionnaire data. Results: Overall, AIV prevalence was 7.73% (n = 45) with 7.39% and 7.92% in Dhamrai and Gazipur Sadar sub-districts, respectively. In AIV-positive samples, the prevalence of A/H5N1, A/H5N2, A/ H9N1, and A/H9N2 was 31.11%, 28.89%, 6.67%, and 8.89%, respectively. None of the samples were positive for N6 and N8. The odds ratio (OR) of AIV infection was 1.15 in broiler versus layer and 2 in Sonali versus layer chickens. The OR was 1.95 for medium versus small, 2.6 for large versus small flock size, 1.5 for moderate versus good biosecurity, and 2.92 for poor versus good biosecurity practicing farms. Conclusion: The results demonstrated that A/H5N1, A/H5N2, A/H9N1, and A/H9N2 are circulating in asymptomatic chickens of selected areas. Strict farm biosecurity practices and avoiding higher flock density are recommended to prevent AIV spread in the study. J. Adv. Vet. Anim. Res., 8(1): 51-57, Mar 2021 http://doi.org/10.5455/javar.2021.h484